(untitled) (Global Conference on Medical and Health Sciences, 2026)
The investment activities of commercial banks play a crucial role in the development of a country’s economy. Banks not only allocate funds through deposit mobilization and lending, but also create investment attractiveness in financing strategic projects. In this process, legal foundations play a significant role, as they regulate relations between banks and clients, reduce financial risks, and ensure transparency in investment activities. National legislation, financial and banking regulations, as well as financial management standards, provide a framework for commercial banks to conduct stable and effective investment activities. Therefore, legal norms serve as a key instrument in enhancing the investment attractiveness of banks.